The Life and Work of Galileo - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
The author presents the main results of his long-term studies on the life and the work of Galileo Galilei within the group of OBI. He mentions his most important publications from this area and points to some problems that are worth elaborating upon in the future.